O trabalho do assistente social em entidades e organizações “vinculadas” à Política de Assistência Social na região do Campo Limpo – São Paulo - SP - Silva, Francisca Tatiana Sousa da (2019)
This dissertation aimed to reflect on the processing of the work of the Social Worker in Entities and Organizations that historically operationalize the social assistance services of the Social Assistance Policy in the Campo Limpo region - São Paulo - SP. Seizing the determinations imposed by the employment relationship, the articulation with Social Assistance Policy and the relationship with the profession. In order to do so, the use of qualitative research and thematic oral history to approach the work that these professionals develop, and capture the dynamics of social relations, the experiences, experiences and challenges of the Social Worker in daily life. Historically, the State transfers the operationalization of Social Assistance Policy services to "third parties" - which, as we know it today, is marked by philanthropy, with focal, fragmented, discontinuous actions, and by Christian humanist thinking. It can be seen that the transfers from the functions of the State to the Entities and Organizations are part of a process of productive restructuring of the bourgeois state in contemporary capitalism. The state makes everything for the capital and minimum for the class that lives of the work, in a process that contemplates losses of hard earned rights; strategies of refilanthropization and outsourcing of the services of public policies in general (here we will speak specifically of the policy of Social Assistance), which favor the accumulation of capital. However, such Entities and Organizations make up the SUAS, are linked to the policy and, in part, contribute to the implementation of the Assistance Policy. This study has as a guide that the Social Worker is a salaried worker, who sells his work force in the market, not having the means and conditions to carry out his work, that is under the dominion of the employers, having, therefore, a relative autonomy technical and political. The professional is an integral part of the working class, which experiences all the mystification, precariousness and invisibility of the work produced by the capitalist mode of production. Their daily work is crossed by the dismantling of public policies in general (both in their work with users and in their lives) and also by the implications of the Institution x Care Policy relationship and the goals and values of each institution. One of the great challenges is not to lose the Ethical-Political Project of the profession of sight